2015
DOI: 10.1111/1752-1688.12366
|View full text |Cite
|
Sign up to set email alerts
|

Apportionment of bioavailable phosphorus loads entering Cayuga Lake, New York

Abstract: The integration of the phosphorus (P) bioavailability concept into a P loading analysis for Cayuga Lake, New York, is documented. Components of the analyses included the: (1) monitoring of particulate P (PP), soluble unreactive P (SUP), and soluble reactive P (SRP), supported by biweekly and runoff event‐based sampling of the lake's four largest tributaries; (2) development of relationships between tributary P concentrations and flow; (3) algal bioavailability assays of PP, SUP, and SRP from primary tributarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
2
19
1
Order By: Relevance
“…Seminatural land cover was estimated to be have a stronger positive influence on EQR TDI than the negative influence of either TP or SRP (Supplemental Tables S4.1, S5.1, S5.2, S6), and combined evidence from different modeling approaches shows that land cover had an overriding influence on the ecological response, which is in line with other studies that also found a hierarchy of stressors from land cover, followed by physicochemical (e.g., sediment and nutrient concentrations) and hydromorphological (e.g., river bed and riparian corridor characteristics) variables (Villeneuve et al, 2018). Here, seminatural land cover is likely acting as a proxy for other factors (Segurado et al, 2018), such as varying bioavailability of P fractions (Ellison and Brett, 2006; Prestigiacomo et al, 2016; Stutter et al, 2018), river morphology, riparian and/or aquatic habitat structure, and absence of toxic contaminants (e.g., herbicides). In addition, the bioavailability of P forms has been shown to vary between 12 and 73% for TP and between 6 and 81% for particulate P in catchments dominated by different land cover types (Ellison and Brett, 2006; Egemose and Jensen, 2009; Poirier et al, 2012; Baker et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seminatural land cover was estimated to be have a stronger positive influence on EQR TDI than the negative influence of either TP or SRP (Supplemental Tables S4.1, S5.1, S5.2, S6), and combined evidence from different modeling approaches shows that land cover had an overriding influence on the ecological response, which is in line with other studies that also found a hierarchy of stressors from land cover, followed by physicochemical (e.g., sediment and nutrient concentrations) and hydromorphological (e.g., river bed and riparian corridor characteristics) variables (Villeneuve et al, 2018). Here, seminatural land cover is likely acting as a proxy for other factors (Segurado et al, 2018), such as varying bioavailability of P fractions (Ellison and Brett, 2006; Prestigiacomo et al, 2016; Stutter et al, 2018), river morphology, riparian and/or aquatic habitat structure, and absence of toxic contaminants (e.g., herbicides). In addition, the bioavailability of P forms has been shown to vary between 12 and 73% for TP and between 6 and 81% for particulate P in catchments dominated by different land cover types (Ellison and Brett, 2006; Egemose and Jensen, 2009; Poirier et al, 2012; Baker et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the bioavailability of P forms has been shown to vary between 12 and 73% for TP and between 6 and 81% for particulate P in catchments dominated by different land cover types (Ellison and Brett, 2006; Egemose and Jensen, 2009; Poirier et al, 2012; Baker et al, 2014). Some land cover types, such as agriculture and urban land use, make TP more bioavailable (Ellison and Brett, 2006; Prestigiacomo et al, 2016), while TP from seminatural land cover is likely to be less bioavailable (Stutter et al, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…Nearly 40% of the total tributary inflow to the lake, as well as 3 point-source discharges, enter its southern end. Large quantities of sediment (Effler et al 2010), P (Prestigiacomo et al 2014), and dissolved color (Effler et al 2015) are delivered to the southern end of the lake by the tributaries during runoff events. A shallow region, designated "the shelf," with a maximum depth of 6 m extends 1.6 km from the southern end of the lake before a sharp drop-off in depth ( Fig.…”
Section: System Descriptionmentioning
confidence: 99%
“…Cayuga Lake is the subject of a total maximum daily load (TMDL) development process resulting from phosphorus impairment to its southern shelf [20]. Movement of phosphorus in the watershed is runoff-driven, and approximately 95% percent of the bioavailable phosphorus load entering Cayuga Lake is nonpoint in origin [21]. High discharge periods produce most of the bioavailable phosphorus loading in the Fall Creek and Cayuga watersheds [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Historic monitoring has examined a diversity of Cayuga Lake's tributaries [32], but has largely focused on bigger tributaries that drain into the southern portion of the lake [21][22][23][24][25]. The motivation for major studies has included large scale undertakings, such as the Cornell lake source cooling project [33], and the ongoing TMDL development process that began in 2013 [20].…”
Section: Introductionmentioning
confidence: 99%